Record of Acanthocephala on Shortfin Scad (Decapterus macrosoma Bleeker, 1851) from the Southern Coast of the Special Region of Yogyakarta, Indonesia - Priscilla Yolanda Pramesti Kolokaring; Rizka Fauziana Syarifah; Hanindya Fairuzia Hidayat; Niken Astuti; Murwantoko Murwantoko; Eko Setyobudi (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2025)
Acanthocephala is a parasite commonly found in the digestive tract of fish. This study aimed to determine the prevalence and mean intensity of Acanthocephala infecting the shortfin scad (Decapterus macrosoma) caught from the southern coast of Yogyakarta and to identify those parasites by morphological approach. A total of 221 samples of fish were obtained from local fishermen operating in fishing grounds along the southern coast of the Indian Ocean in the Special Region of Yogyakarta. The fish samples were measured for total length (TL) and weight and dissected to examine for the presence of Acanthocephala. Parasite samples were collected from the digestive tract of shortfin scad and preserved in absolute ethanol for further identification. Data analysis focused on calculating prevalence and mean intensity of infection. The results showed that the prevalence of Acanthocephala infection was 16.3%, with a mean intensity of 1.9 larvae/host. Both the prevalence and the mean intensity tended to increase with increasing fish length. Most of the shortfin scad (75%) was infected with Acanthocephala at a relatively low intensity (1-2 larvae/host). The highest intensity of Acanthocephala infection was 13 larvae/host and was only found in one fish. Morphological identification indicated that the genus infecting shortfin scad was Acanthocephalus (Koelreuther, 1771). Keywords: Acanthocephalus, biological tag, morphology, parasite, prevalence